The Design and Execution of Performance Management Systems at State Level: A Comparative Analysis of Italy and Malaysia. Issue 9 (29th July 2017) - Bianchi, Carmine; Xavier, John Antony
ABSTRACT: This comparative study analyses the experience of Italy and Malaysia in the design and execution of performance management systems at the state level. The article investigates how performance management systems have changed over the past decades, the motivations behind their metamorphoses, their common elements across the two countries, and what accounts for the respective progress. It also investigates the role that the institutional framework plays in making performance management systems robust. The study presents policy recommendations on how governments can create more robust performance management systems for enhanced accountability and transparency in an age of resource constraint.